Answer :

Now, as a,b,c are in GP.


Using the idea of geometric mean we can write –


b2 = ac …(1)


Put in the LHS of the given equation to be proved –


LHS = a(ac + c2) {putting b2 = ac}


LHS = a2c + ac2


LHS = c(a2 + ac)


Again put ac = b2


LHS = c(a2 + b2) = RHS


L.H.S = R.H.S


Hence proved


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

The product of thRD Sharma - Mathematics

Express <imRS Aggarwal - Mathematics

If a, b, c are inRS Aggarwal - Mathematics

Express <imRS Aggarwal - Mathematics

Prove that RS Aggarwal - Mathematics

If a, b, c are inRS Aggarwal - Mathematics

The sum of n termRS Aggarwal - Mathematics

If a, b, c, d areRS Aggarwal - Mathematics

Evaluate :
</p
RS Aggarwal - Mathematics

The first term ofRS Aggarwal - Mathematics